ST-18AB Influence of rubber content of concrete on local impact damage - Sia, Grace Xing Rong (2018)
To address the large drop in the overall capacity of structures caused by fragment impacts during crater formation, a study is conducted which aims at investigating the effect of two different types of crumb rubber – running track rubber (SBR) and rubber tyre in concrete for the enhancement of concrete’s energy absorption abilities against dynamic impact. Crumb Rubber Concrete (CRC) was prepared by replacing 20% of coarse aggregates with the abovementioned types of crumb rubber. Light-gas gun tests were carried out on the concrete specimens. In total, twenty-two concrete samples were subjected to high velocity dynamic impact test, of which, 10 concrete samples were attached with strain gauges. Stainless Steel Type 316 projectile of 12 mm diameter is launched with striking velocities from 109m/s to 177m/s and damage of the concrete targets were assessed. The capability of CRC in providing resistance against high velocity impact damages were assessed by the measuring the crater depth, area and volume. Influences of the types of aggregates and incident velocity of the projectile on the crater depth, impact crater area and volume were discussed. In addition, strain waves of the concrete specimens were studied to determine damping effects of the different type of aggregates. This is done by calculating the percentage of reduction of strain waves signals at 22.5mm and 52.5mm diagonally away from the centre of the concrete specimens. Results showed CRC increased the impact crater depth, crater area and volume of the concrete specimens. However, SBR aggregates exhibited more consistent structural damage results, have smaller impact crater area and volume of as compared to rubber tyre aggregates upon high velocity dynamic impact. Furthermore, replacing a portion of coarse aggregates with rubber aggregates proved to be able to increase the energy absorption abilities of the concrete specimens and SBR aggregates proved to have better damping abilities than rubber tyre aggregates. Therefore, SBR aggregates are more effective as a coarse aggregate replacement as compared to rubber tyre aggregates.